IMPROVING THE SYSTEM OF MASS HEALTH EXAMINATIONS OF CHILDREN - Maria O. Revnova; Dmitryi Ya. Volkov; Larisa V. Sahno; Inna V. Koltunceva; Svetlana V. Bairova; Tаtjana V. Mishkina; Valentina I. Bulicheva; Tatjana V. Policuk; Aleksandr Ya. Volkov; Irina M. Gaiduk ("Paediatrician" Publishers LLC, 2017)
Screening health examinations of children are a powerful tool for monitoring the health of the younger generation, in other words, it is an active method of dynamic monitoring of children's health. The objective of screening is early detection of disorders with further linkage to care, follow-up care, and comprehensive treatment of patients. Currently, the Russian Federation has a regulatory document on the conduct of preventive periodic and preliminary examinations (Order of the Ministry of Health of the Russian Federation No.1346). The problem is the lack of time and resources, which leads to a formal approach to this necessary part of preventive measures. The article suggests ways out of the current situation that would satisfy both the heads and the district pediatricians themselves.